Temperature effects on the microscopic haploid stage development of laminaria ochroleuca and sacchoriza polyschides, kelps with contrasting life histories - Pereira, T. R. (2014)
Kelp forests are one of the most diverse and productive ecosystems worldwide. Global climate change and human exploitation threaten the stability of many of these ecosystems.